Repurposing the utilisation of data in Agrobiodiversity Information System - Mohamad Zulkifly Zakaria @ Mustafa (2022)
AgrobIS or Agrobiodiversity Information System is a repository system that was developed to store and manage data on genetic resources generated by studies conducted in MARDI. The repository contains data on PGRFA, livestock, biotechnology, arthropods and microbes. These data are not only important for conservation purposes and as a reference for future generations but also essential for developing or producing other systems such as dashboards. Expanding the use of these data to be implemented and integrated in other systems is important as it would highly benefit MARDI in the future. However, repurposing the data for newer decision making information system was difficult and problematic as the data in the database were not properly recorded, formatted and collated which impedes and delays the database querying and retrieval of required data during the data transformation process. Thus, this paper describes the steps taken to enhance the database query and retrieval times during the repurposing of data available in the AgrobIS system which includes the Extract, Transfer and Load (ETL) process and the use of a tool to accommodate the ETL process known as Talend Open Studio for Data Integration. Paddy data was specifically chosen for data transformation as it covered the most accessions available in the AgrobIS database compared to other categories of genetic resources.